La forme scolaire en confinement : enseignants et parents à l’épreuve de l’enseignement à distance - Ria, Luc; Rayou, Patrick (Formation et profession : revue scientifique internationale en éducation, 2020)
Confined to their homes, educators have shifted the traditional teaching centre of gravity to the family. Are the resultant adjustments temporary, or do they foreshadow major and lasting changes in education delivery? Two qualitative studies were conducted in teachers and parents of students aged 7 to 15 years. Results show old tensions arising in the relationships between in and outside of class, along with new tensions over the digital methods that are meant to restore learning continuity. The results also point to promising long-term solutions that integrate a diversity of perspectives on education.
Publisher: Centre de recherche interuniversitaire sur la formation et la profession enseignante (CRIFPE)
Keywords: Forme scolaire; Learning mode; activités d’enseignement apprentissage; enseignement à distance; formation des enseignants; remote learning; teacher training; teaching and learning activities